Exploring clinical environmental awareness and its impact on patient safety - Green, Cheryl Ann (44th Biennial Convention (28 October - 01 November 2017), 2017)
Citation Key Alias: lens.org/172-960-066-273-809
Keywords: dept.nur; ⛔ No DOI found

Interprofessional health promotion - Green, Cheryl Ann (44th Biennial Convention (28 October - 01 November 2017), 2017)
Citation Key Alias: lens.org/131-376-763-026-053
Keywords: dept.nur; ⛔ No DOI found

Understanding the complexities of the effects of incivility on the victim and using mindfulness to heal - Green, Cheryl Ann (International Journal of Health, Wellness & Society, 2018)
The complexity of the human body is such that any disturbances to its homeostatic state, unreversed, can lead to the development of illness or disease. When one considers the terminology of incivility as a concept, one does not automatically equate this concept with disease or illness. However, incivility left to persist in work environments can prove mentally and physically damaging to the victim. Mindfulness can be used as a means to help nurses experiencing workplace incivility, to begin the process of emotional and physical healing.
3 citations (Crossref) [2023-10-31]
Keywords: EMOTIONS (Psychology); HOMEOSTASIS; Illness; Incivility; MINDFULNESS; Mindfulness; NURSES; Nurses; WORK environment; Work Environment; dept.nur; peer-reviewed

Complimentary Care: When Our Patients Request to Pray. - Green, Cheryl Ann (Journal of Religion and Health, 2018)
Prayer is viewed in modern medicine as a complimentary alternative treatment. However, to many patients, it is a source of hope and comfort. Patients, when facing illness, advanced disease, disability or death, can benefit from prayer. For healthcare providers, comfort with praying with patients can be deemed as unprofessional conduct or blurred therapeutic boundaries, particularly, when prayer is offered to patients' unsolicited by the patient or their family member(s). Therefore, it is imperative that healthcare providers await the request of prayer by the patient before prayer is initiated.
5 citations (Crossref) [2023-10-31] Place: United States Green, Cheryl Ann. Southern Connecticut State University, 501 Crescent Street, Jennings Hall, Office 121, New Haven, CT, 06515, USA. Greenc16@southernct.edu.
Keywords: *Attitude of Health Personnel; *Delivery of Health Care; *Faith Healing; *Pastoral Care/mt [Methods]; *Religion; *Spirituality; Attitude of Health Personnel; Delivery of Health Care; Faith Healing; Family; Healthcare providers; Humans; Nurse's Role; Nurses; Pastoral Care; Patients; Prayer; Religion; Religion and Medicine; Spirituality; dept.nur; family; health care delivery; health personnel attitude; human; nurse attitude; pastoral care; peer-reviewed; procedures; religion; spiritual healing

Identification of patients' spiritual needs using a spiritual health assessment tool - Green, Cheryl Ann (Creating Healthy Work Environments, 2019)
Citation Key Alias: lens.org/090-145-772-380-333 tex.type: [object Object]
Keywords: dept.nur; ⛔ No DOI found

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
7 citations (Crossref) [2023-10-31]
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace

Can't breathe - Green, Cheryl Ann (Aji, 2020)
Keywords: dept.nur; ⛔ No DOI found

Enough is enough: teaching nurses not to tolerate workplace violence and incivility - Green, Cheryl Ann (Minority Nurse, 2020)
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Enough Is Enough: Confronting Workplace Bullying and Incivility - Green, Cheryl Ann (STTI, 2020)
tex.ids: greenEnoughEnoughConfronting2020
Keywords: dept.nur; ⛔ No DOI found